Pathogenic Candida species differ in the ability to grow at limiting potassium concentrations - Hušeková, B; Elicharová, H; Sychrová, H (Canadian journal of microbiology, 2016)
A high intracellular concentration of potassium (200-300 mmol/L) is essential for many yeast cell functions, such as the regulation of cell volume and pH, maintenance of membrane potential, and enzyme activation. Thus, cells use high-affinity specific transporters and expend a lot of energy to acquire the necessary amount of potassium from their environment. In Candida genomes, genes encoding 3 types of putative potassium uptake systems were identified: Trk uniporters, Hak symporters, and Acu ATPases. Tests of the tolerance and sensitivity of C. albicans, C. dubliniensis, C. glabrata, C. krusei, C. parapsilosis, and C. tropicalis to various concentrations of potassium showed significant differences among the species, and these differences were partly dependent on external pH. The species most tolerant to potassium-limiting conditions were C. albicans and C. krusei, while C. parapsilosis tolerated the highest KCl concentrations. Also, the morphology of cells changed with the amount of potassium available, with C. krusei and C. tropicalis being the most influenced. Taken together, our results confirm potassium uptake and accumulation as important factors for Candida cell growth and suggest that the sole (and thus probably indispensable) Trk1 potassium uptake system in C. krusei and C. glabrata may serve as a target for the development of new antifungal drugs.
Keywords: morphologie; Candida tropicalis; draslík; homéostasie du potassium; potassium homeostasis; Candida glabrata; genom fungální; Genome, Fungal; Potassium; morphology; Candida albicans; Candida